Sport Organization Employee Performance: Skills, Creativity and Innovation - Andrefson, Edo; Fikriando, Eko; Relifra, Relifra (Journal of Business Management and Economic Development, 2023)
Good performance can have a tremendous impact on the organization concerned. The favored performance increase does not quickly materialize however calls for a protracted method. Good employee performance will be useful for companies or institutions in achieving their goals. This research is to look at the factors that influence employee performance at KONI Sungaipenuh City. On this have a look at, soft skills have a significant impact on creativity. Likewise, creativity has a significant effect on employee performance and soft skills have a substantial effect on employee performance through creativity. in the meantime, other hypotheses on this take a look at implying that the speculation is rejected or has no widespread impact. The data analysis approach to be able to be used in this examination is to apply a structural equation modeling. SEM offers capabilities for path analysis, the path analysis that will be used in this research is partial least squares (PLS), using Smart PLS 4.0 software. The sample consisted of 42 respondents from the employees of the KONI Sungaipenuh City